Pengembangan Media Pembelajaran Interaktif Berbasis Nearpod Untuk Meningkatkan Hasil Belajar - Rita Syofyan; Muvi Dellatul Husni (Universitas Negeri Padang, 2023)
Interactive learning media based on Nearpod is a media were developed to make learning processes more interactive. This media will offer a assortment of elements that might be utilized to engage students directly in the educational experience and make it more charming and meaningful. Furthermore, this media will simplify it for understudies to comprehend the idea of realizing, which can move along student learning outcomes. This exploration is an examination and improvement research with the advancement model utilized utilizes a 4-D model, consisting of four defining, planning, developing, and disseminating. The consequences of the master approval test demonstrated that this media was practical concerning content, with a typical worth of 80% and for the plausibility of the media it got a typical worth of 83.3% with a truly possible class. The aftereffects of the assessment master approval test also indicate this media are suitable for use as an evaluation test. The aftereffects of the common sense test showed that this media was very practical for usage in learning, with an average rating of 88.3% for teachers and 89.8% for students. Interactive media based on Nearpod is also efficient for improving student learning outcomes for national income economics lessons.